FLUID CONTROL OF LOCALIZED MINERAL DOMAINS IN LIMESTONE PRESSURE SOLUTION STRUCTURES - Evans M.A.; Elmore R.D. (My University, 2006)
Grain-to-grain and stylolitic solution structures in two central Appalachian Siluro-Devonian limestone macroscale folds contain one of four distinct mineral assemblages that are characterized by the dominant iron-phase mineral present: (1) chlorite±illite±pyrite calcite±quartz±TiO2±goethite, (2) chlorite±illite±pyrite altered to iron oxide/hydroxide ±calcite ±quartz±TiO2, (3) chlorite ±illite± magnetite±calcite±quartz, and (4) chlorite±illite±goethite±calcite± TiO2. Optical reflectance microscopy and SEM-EDS was used to characterize the mineralogy and mineral morphology of these structures. Geochemical modeling was used to constrain the conditions of formation and preservation. The primary control on solution structure mineral assemblage was the redox conditions present in the solution structures during burial and deformation. The redox conditions on the microscale may have been controlled by the local fluid chemistry and the presence-absence of hydrocarbons and organic acids within the formation fluids, and the influx of externally derived fluids by fracture formation during the folding process. The wide variation in mineralogy of the solutions structures shows that they were 'chemical factories' where a variety of chemical reactions took plase during rock dissolution. In particular, the formation of authigenic magnetite in solution structures has significant implications for paleomagnetic applications, and use of anisotropy of anhysteretic remanent magnetization and anisotropy of magnetic susceptibility fabrics. © 2005 Elsevier Ltd. All rights reserved.
Keywords: FLUID FLOW; MAGNETITE; PRESSURE SOLUTION; STYLOLITES; Devonian; Paleozoic::Devonian; Палеозой::Девонская